Managing Trust in the Implementation of Corporate Social and Environmental Responsibility Programs in North Kalimantan Province - Ferdi Manurun Tanduklangi, Muh. Akmal Ibrahim , Moh. Thahir Haning , Badu Ahmad (South Eastern European Journal of Public Health, 2025)
Aims: This study is intended to determine the implementation of managing trust in the implementation of the Corporate Social and Environmental Responsibility Program in North Kalimantan Province. The following that contained in the Regulation of the Governor of North Kalimantan Province Number 11 of 2023. Methods: The data are then compiled in a qualitative study. Results: The results of this study indicate that the implementation of Managing Trust in the Implementation of the Corporate Social and Environmental Responsibility Program in North Kalimantan Province has not been implemented optimally, many things need to be improved, closely related to the differences in power possessed by each stakeholder, which is very vulnerable to causing social conflict on each party.